The Influence of Fatwas Regarding Illegitimate Children at The Courts in Indonesia - Mustafa, Ahsin Dinal; Fakhruddin, Fakhruddin; Roibin, Roibin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
One of the complex and important issues in the context of Islamic family law is the phenomenon of illegitimate children. Among the institutions recognized by society as providing solutions through fatwas (decision) are the Indonesian Islamic Scholars Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah. This paper aims to explore and analyze this issue in more depth, presenting a perspective that includes aspects of law and society that are manifest in a fatwa, as well as summarizing the significance of the fatwa for decisions in court. This paper uses a qualitative normative approach in the form of library research and analysis of documents in the form of fatwas and decisions that quote fatwas as ratio decidendi. Several decisions use this fatwa as a source of material law because there is no explanation regarding the civil rights given to illegitimate children from their biological fathers in the Constitutional Court decisions or other regulations. In several decisions, fatwas are used by judges in the ratio decidendi decisions in Indonesia. However, the result is that there is disparity in decisions due to differences in the judges' interpretation of the fatwa they use.